Aplicação do conceito de City Information Modelling (CIM) associado ao uso de tecnologias inteligentes em cidades consolidadas - Souza, Letícia de (2021)
The serious social and environmental problems arising from the intense urbanization of cities, listed as the main challenges for city managers in the 21st century, require the use of new tools for efficient urban management since conventional approaches to urban planning are inflexible to face these challenges. Within this context, City Information Modelling (CIM) becomes an important tool for urban planners to manage the city's infrastructure based on sound information and thus adapt to constant changes. However, the absence of a complete application of CIM and of an established concept has been observed in the literature. Thus, as a general objective, it was sought to examine and synthesize the information about the CIM present in the literature, and thus, to identify and enable the contributions of CIM for planning and urban decision-making in consolidated cities. To this end, it was used a systematic literature review and bibliometric analyses enabled the identification of the interoperability required for a CIM application; the computational tools that would support the implementation; its potentialities; and the application initiatives, as well as the research trends and existing gaps. With these results, it was possible to delimit maturity levels towards the CIM application, which provided the pertinent characteristics to each implementation level. To understand the national scenario of the use of technologies that assist urban management, a survey was conducted, applied to servers of the city hall of six Brazilian cities, and allied to documentary research were verified the implemented technologies, the results obtained, the motivations and the difficulties faced in the current implementations. Therefore, these results served as a basis for the proposition of guidelines for CIM implementation, which may guide technological and CIM implementations in the Brazilian context, in order to mitigate the potential barriers reported by the representatives of the cities. As contributions, it can be highlighted the presence of a conceptualization for the CIM, identification of several technological tools with great potential of use and suggestions for improvements to expand the predictive capacity of these tools when integrated into the CIM platform. The allocation of the case studies of the literature and of the Brazilian cities in the CIM maturity levels, provided important contributions for the development of goals and progression towards the establishment of the CIM, as well as, the demonstration of some model cities in more advanced levels of technology use, demonstrated how such use is feasible, and the benefits granted by these experiences were evidenced. Finally, the development of the CIM implementation guidelines, allowed us to propose solutions to mitigate the challenges reported by representatives of Brazilian cities and match the necessary conditions of the CIM. As a managerial contribution, the results can be used for cities to identify their implementation levels, and thus have sufficient repertoire to elaborate action plans for the application of the CIM.